The Wallachians in Hungary - Grzesik, Ryszard (Balcanica Posnaniensia. Acta et studia, 2021)
The article describes the presence of the Wallachians in the Hungarian Kingdom on the basis of sources from the earliest mentions on this population until the early modern period. In the Gesta Hungarorum the Wallachians were described as pastores Romanorum, the former inhabitants (together with the Slavs) of the region between the Great Hungarian Plain and the western part of Transylvania, conquered by Hungarian newcomers. In the description of the Eastern Europe (1308) Wallachians were identified with the pastors of the Romans. According to Simon of Kéza they transferred the knowledge of writing to the Szeklers. From the point of view of the Renaissance Italian and Hungarian humanists, they were the descendants of former Roman soldiers from the Dacia Traiana province. In the Hungarian documents, the Wallachian settlement in Transylvania is confirmed for the beginning of the 13th century, however, the majority of information about them derived from the end of this period. The Wallachian presence was observed in the southern parts of Carpathians and western Transylvanian mountain ranges. Their migrations were reported in the Eastern and Western Carpathians, the main direction ran from Máramaros (Maramureş) (1320) towards Kysuce-Zvolen (Zolyom) region in the 16th century and the border with Moravia. At first, migrated the East Romance population with the great (or dominant) contribution of the Slavic (probably Bulgarian) element. In the sources on Máramaros from the end of 14th century the Wallachian settlers were identified with the Ruthenians. By contrast, west of Spiš (Zips, Szepes) the Slovaks and the Poles were called the Wallachians. There can be also the evolution of character of the Wallachian settlement observed. First, it had primarily ethnic attributes. Later, it came in specific socio-economic forms, connected with the colonization of population (mainly the Slavs), primarily in the mountains. Some representatives of the Wallachian population (kenezii, vojevodae) were ennobled and became the part of the Natio Hungarica. They accepted the Catolicism and Hungarian identity. The rest of the population preserved the Orthodox faith and was subjugated. The Wallachians dealt not only with the transhumant economy, but also the agriculture. Moreover, they were the soldiers (guards) on the borders or communication routes.